Case report: Acute right ventricular dysfunction after surgery in a pregnant patient with congenital heart disease and aortic dissection - Hao, Junhai; Liu, Siyi; Sun, Tucheng; Lei, Liming (Frontiers in Cardiovascular Medicine, 2023)
Pregnant women with aortic dissection are hemodynamically outmost complex patients. The two major diagnoses that should be considered in pregnant patients with congenital heart disease (CHD) and acute type A aortic dissection presenting with postoperative right ventricular dysfunction are pulmonary thromboembolism and right ventricular infarction. We present a rare case of postoperative right ventricular dysfunction in pregnant women with CHD and acute aortic dissection, which was diagnosed by pulmonary computed tomography angiography and treated by percutaneous coronary intervention.